Pulmonary puzzles: salivary gland-type tumors of the lung and their metastatic equivalents - Olteanu, Gheorghe-Emilian; Brcic, Luka (Memo - Magazine of European medical oncology, 2024)
Summary In the last decade, the understanding of lung neoplasms, particularly rare salivary gland-type tumors (SGT), has deepened significantly. This review intends to spotlight the latest findings, particularly emphasizing the differentiation between primary and metastatic SGTs in the lung.